Advancing Library Systems: The Impact of OPACs on Research and Learning - V. Senthur Velmurugan (International Journal of Electronics Automation, 2024)
The Online Public Access Catalogue (OPAC) has emerged as a transformative tool in library science, reshaping the landscape of information access and retrieval. This abstract explores the historical evolution, functionalities, and broader implications of OPAC systems in modern libraries. Initially conceived as digital replacements for traditional card catalogs, OPACs have undergone significant advancements, leveraging internet technologies to offer users unprecedented access to library collections. From basic search functionalities to sophisticated query options, OPACs have evolved into dynamic platforms that facilitate efficient exploration and retrieval of diverse library resources, including books, journals, multimedia materials, and digital assets. The abstract examines the key features and functionalities of contemporary OPACs, including advanced search capabilities, personalized user interfaces, and seamless integration with other library services. Furthermore, it highlights the role of OPACs in promoting information literacy and supporting diverse user needs by providing remote access, real-time availability status, and tailored recommendations. Moreover, the abstract discusses the broader impact of OPACs on library management practices, user engagement, and the dissemination of knowledge in the digital age. It underscores OPACs' role as essential tools for fostering lifelong learning, research, and intellectual discovery in academic, public, and specialized library settings. In conclusion, the abstract emphasizes the significance of OPACs as foundational components of contemporary library infrastructures, driving innovation, accessibility, and collaboration in the pursuit of knowledge dissemination and enrichment
Keywords: Advanced search; Boolean operators; Database; and reserve materials; interlibrary loan; search; subject headings